2019
DOI: 10.1038/s41598-019-44413-x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus sequence divergence preserves p7 viroporin structural and dynamic features

Abstract: The hepatitis C virus (HCV) viroporin p7 oligomerizes to form ion channels, which are required for the assembly and secretion of infectious viruses. The 63-amino acid p7 monomer has two putative transmembrane domains connected by a cytosolic loop, and has both N- and C- termini exposed to the endoplasmic reticulum (ER) lumen. NMR studies have indicated differences between p7 structures of distantly related HCV genotypes. A critical question is whether these differences arise from the high sequence variation be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 77 publications
0
14
0
Order By: Relevance
“…In both cases, solid-state NMR was compared to solution-state NMR data obtained in micelles, and Opella and coworkers first identified the localization of the transmembrane domains of p7 and Vpu in lipid bilayers. Unfortunately, the full p7 structure in lipids could not yet be solved, as this would help to resolve contrasting data between different detergent-based solution NMR studies [ 145 , 146 , 147 , 148 , 149 ]; the membrane might actually play a central role in determining p7 structure and oligomerization.…”
Section: Examples Of Solid-state Nmr Studies On Viral Proteinsmentioning
confidence: 99%
“…In both cases, solid-state NMR was compared to solution-state NMR data obtained in micelles, and Opella and coworkers first identified the localization of the transmembrane domains of p7 and Vpu in lipid bilayers. Unfortunately, the full p7 structure in lipids could not yet be solved, as this would help to resolve contrasting data between different detergent-based solution NMR studies [ 145 , 146 , 147 , 148 , 149 ]; the membrane might actually play a central role in determining p7 structure and oligomerization.…”
Section: Examples Of Solid-state Nmr Studies On Viral Proteinsmentioning
confidence: 99%
“…Solution NMR was also used to determine the structure of another helical membrane protein, the p7 cation channel from hepatitis C. Chou and colleagues determined a hexameric assembly of the p7 protein in DPC micelles, in which the protein formed a funnel-like structure with a flower shape [ 78 ]. However, this structural model has been disputed by Zitzman, Schell and colleagues, who have presented evidence that in DPC micelles, the protein is monomeric [ 79 , 80 ]. The latter investigation used a higher excess of DPC than Chou et al [ 81 ], who subsequently showed that p7 does form a hexameric structure in isotropic bicelles.…”
Section: Solution Nmrmentioning
confidence: 99%
“…Phospholamban (PNL), a homopentamer expressed in sarcoplasmic reticulum that controls intracellular Ca 2ϩ levels through its phosphorylation state, is another example where solution NMR structure determined in DPC micelles (PDB code 1ZLL) (143) differs significantly from the one obtained in lipid bilayer by a combination of solution and solid-state NMR methods (PDB code 2KYV) (136). The "bellflower" model originally proposed (Fig.…”
Section: Structural Discrepanciesmentioning
confidence: 99%